A class of entanglement witnesses and a realignment-like criterion - Vahid Jannesary; Vahid Karimipour; Dariusz Chruściński (Scientific Reports)
Abstract We present a multi-parameter family of positive maps between spaces of arbitrary but finite dimensions. This framework facilitates the construction of Entanglement Witnesses (EWs) specifically designed for systems living in $$d_1× d_2$$ dimensions. A sufficient condition for positivity is presented. Interestingly, it is shown that all EWs constructed this way are equivalent to a single realignment-like criterion which for $$d_1$$ and $$d_2$$ are different is in general stronger than the original realignment criterion. We illustrate effectiveness of this criterion considering examples of Positive Partial Transpose entangled states in $$ 4× 4$$ and $$3× 4$$ dimensions.